2005
DOI: 10.1007/s10459-005-1404-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Students’ Perceptions of Learning Compulsory Foundation Biochemistry in the Health Sciences Professions

Abstract: Student approaches to learning vary from surface approaches to meaningful, deep learning practices. Differences in approach may be related to students' conceptions of the subject, perceptions of the learning environment, prior study experiences and performance on assessment. This study aims to explore entering students' conceptions of the unit they are about to study and how they intend to approach their studies. It involved a survey of 203 (of 250) first year students in a cross disciplinary unit in the Facul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 8 publications
1
27
0
Order By: Relevance
“…The students new to biochemistry also tend to use a ''surface approach,'' rather than a ''deep approach,'' to learning [1,2]. Consequently, we were eager to develop learning strategies that would help to motivate students new to biochemistry and promote a ''deep approach'' to learning.…”
Section: Introductionmentioning
confidence: 99%
“…The students new to biochemistry also tend to use a ''surface approach,'' rather than a ''deep approach,'' to learning [1,2]. Consequently, we were eager to develop learning strategies that would help to motivate students new to biochemistry and promote a ''deep approach'' to learning.…”
Section: Introductionmentioning
confidence: 99%
“…Becoming conversant with its specific terminology has been likened to learning a foreign language (Lumpkin Allen, 1997). A student's ability to learn and later apply microbiological and indeed scientific principles in general may be influenced by the perceived difficulty and relevance of the science subjects (Minasian-Batmanian, Lingard, & Prosser, 2005). They may also be influenced by their preconceptions of science.…”
Section: Foundation Knowledge -Relevance and Applicationmentioning
confidence: 99%
“…The first example of scholarly studies of teaching and learning in the health sciences addressing the ways in which students build on their prior understanding concerns a compulsory foundation biochemistry course for first-year undergraduates across the health sciences at an Australian university (Minasian-Batmanian, Lingard & Prosser 2005). The study took as starting point "a lack of literature on students' perceptions of learning topic areas that are both compulsory and only foundation studies in a focussed, professionally oriented curriculum, which is highly constrained by a graduate skills outcome" (p. 280), and an insight from existing literature that "students' prior orientations to study and their prior understandings of the subject matter and how it is conceived are related to their perceptions of the teaching and learning context" (p. 280).…”
Section: What Do Students Think They Are Learning?mentioning
confidence: 99%
“…From the outset, and even after having studied the course, there were still the same sorts of conceptions of the nature of the overall subject of study, in line with the notions of fragmented and coherent conceptions (Prosser & Trigwell 1999), and the percentages for each response are little changed. Source: Minasian-Batmanian et al (2005:285), (2006:1893 Research has shown that students who have a mainly fragmented prior knowledge are more likely to fail to grasp the goals of the course and to be overwhelmed by it and are then likely to take a surface -reproducing or fulfilling perceived course demands -rather than a deep approach with its meaning making intent (Prosser & Trigwell 1999). Also evident is that the surface approach is associated with students failing to grasp critical elements of content and tending to forget content rather fast -which is not to say that they fail their examinations but that they might not have adequate prior knowledge for future courses.…”
Section: What Do Students Think They Are Learning?mentioning
confidence: 99%
See 1 more Smart Citation